Pengaruh Penggunaan Fasilitas Garbarata (Aviobridge) Terhadap Kenyamanan Penumpang di Bandar Udara Halu Oleo Kendari - Fahmi, La Ode Farhan Ezra; Fauziah, Syifa (Jurnal Ground Handling, 2024)
Halu Oleo Airport in Kendari plays a crucial role in enhancing community mobility and fostering local economic growth in the city. With an increasing number of passengers, there is a clear need for facilities that can improve service quality and enhance passenger travel comfort. One such facility is the aviobridge, which provides easier access for passengers during the boarding and deboarding processes compared to using manual stairs or Passenger Boarding Stairs (PBS). This research aims to examine whether there is an influence of the aviobridge facility on the comfort of users at Kendari Airport. This study employs a quantitative method, focusing solely on the use of the aviobridge facility and the comfort of passengers during boarding and deboarding. The population of the research encompasses all passengers utilizing the jet bridge at Halu Oleo Airport. Data were collected through questionnaires distributed to 100 respondents, as well as documentation, literature studies, and data from the AMC unit, utilizing both primary and secondary data types. After data collection, the data were analyzed descriptively and processed using SPSS with testing techniques such as instrument testing, hypothesis testing, and determination coefficient analysis. The research findings indicate a positive influence between the use of the jet bridge facility and passenger comfort. This is based on the T-test results, which showed that the calculated T (17.840) is greater than the table T (1.984) with a significance value of 0.000 (< 5% or 0.05). Therefore, the null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted. Furthermore, the effect size of the aviobridge facility variable (X) is 73.2% on the passenger comfort variable (Y), based on the determination coefficient test results. Descriptive analysis reveals that the statement with the lowest average score is "The interior design of the aviobridge feels modern and is visually appealing" (4.08), followed by "The air conditioning system functions well" (4.15). Based on these findings, it is recommended that Halu Oleo Airport pay more attention to the interior design of the aviobridge and conduct regular maintenance of the air conditioning system to enhance passenger comfort. Keywords: Aviobridge Facility, Jet Bridge Condition, Passenger Comfort